2012
DOI: 10.3389/fpsyg.2012.00467
|View full text |Cite
|
Sign up to set email alerts
|

When Do We Confuse Self and Other in Action Memory? Reduced False Memories of Self-Performance after Observing Actions by an Out-Group vs. In-Group Actor

Abstract: Observing another person performing an action can lead to a false memory of having performed the action oneself – the observation-inflation effect. In the experimental paradigm, participants first perform or do not perform simple actions, and then observe another person perform some of these actions. The observation-inflation effect is found when participants later remember performing actions that they have merely observed. In this case, self and other are confused in action memory. We examined social conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Instead of using a two-step memory test like in the first experiments, we directly asked our participants to choose from three options to answer whether a depicted action had been performed, read, or not presented (no mention was made of the subject in order to be able to use the same formulation in both groups). We have used this one-step procedure repeatedly in former studies and obtained comparable results to the two-step memory test used in Experiments 1 and 2 (e.g., Lindner et al, 2012;Schain et al, 2012).…”
Section: Materials and Proceduresmentioning
confidence: 69%
See 2 more Smart Citations
“…Instead of using a two-step memory test like in the first experiments, we directly asked our participants to choose from three options to answer whether a depicted action had been performed, read, or not presented (no mention was made of the subject in order to be able to use the same formulation in both groups). We have used this one-step procedure repeatedly in former studies and obtained comparable results to the two-step memory test used in Experiments 1 and 2 (e.g., Lindner et al, 2012;Schain et al, 2012).…”
Section: Materials and Proceduresmentioning
confidence: 69%
“…Because our results were not consistent with a sensory-similarity account (Lindner et al, 2010, Exp. 3;Lindner et al, 2012), we have proposed an alternative account building on motor-simulation research. A growing body of literature has shown that observers covertly simulate actions performed by another person as if they are performing these actions themselves (e.g., Grèzes & Decety, 2001;Wilson & Knoblich, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, watching someone else pour water into a glass can lead people to claim mistakenly that they themselves performed this action, dubbed the observation-inflation effect (Lindner, Schain, Kopietz, & Echterhoff, 2012;Schain, Lindner, Beck, & Echterhoff, 2012). Exposure to photographs of actions involving objects in their completed states in Phase 2 (e.g., seeing a photo of an empty water bottle with a full glass of water beside it) also induces false claims of having performed those actions, the photo-inflation effect (Henkel, 2011).…”
mentioning
confidence: 99%
“…Brown et al (2012) argue that this malleable nature of memory serves a socially adaptive function: The content of personal memories merge in the process of social interaction and this, in turn, fosters a sense of collective identity. The work of Lindner et al (2012) suggests that there may be certain boundaries to this effect, however, that are driven by group membership.…”
mentioning
confidence: 99%